APOBEC3B: Future direction of liver cancer research - Yang, Xingyue; Dai, Jing; Yao, Shun; An, Jiaxing; Wen, Guorong; Jin, Hai; Zhang, Li; Zheng, Liming; Chen, Xingyue; Yi, Zhiqiang; Tuo, Biguang (Frontiers in Oncology, 2022)
Liver cancer is one of the most common cancers in the world, and the rate of liver cancer is high due to the of its illness. The main risk factor for liver cancer is infection with the hepatitis B virus (HBV), but a considerable number of genetic and epigenetic factors are also directly or indirectly involved in the underlying pathogenesis of liver cancer. In particular, the apolipoprotein B mRNA editing enzyme, catalytic peptide-like protein (APOBEC) family (DNA or mRNA editor family), which has been the focus of virology research for more than a decade, has been found to play a significant role in the occurrence and development of various cancers, providing a new direction for the research of liver cancer. APOBEC3B is a cytosine deaminase that controls a variety of biological processes, such as protein expression, innate immunity, and embryonic development, by participating in the process of cytidine deamination to uridine in DNA and RNA. In humans, APOBEC3B has long been known as a DNA editor for limiting viral replication and transcription. APOBEC3B is widely expressed at low levels in a variety of normal tissues and organs, but it is significantly upregulated in different types of tumor tissues and tumor lines. Thus, APOBEC3B has received increasing attention in various cancers, but the role of APOBEC3B in the occurrence and development of liver cancer due to infection with HBV remains unclear. This review provides a brief introduction to the pathogenesis of hepatocellular carcinoma induced by HBV, and it further explores the latest results of APOBEC3B research in the development of HBV and liver cancer, thereby providing new directions and strategies for the treatment and prevention of liver cancer.